Role of Human Papilloma Virus in Carcinogenesis of Head and Neck Squamous Cell - Rahman, Sukri; Musyarifah, Zulda (Frontiers on Healthcare Research, 2024)
Background: Head and neck squamous cell carcinoma (HNSCC) is a malignancy that occur in head and neck region and originates from squamous epithelial cell in the upper respiratory tract mucosa. This malignancy has a high heteregenicity. Carcinogenesis due to HPV infection has a different moleculer pathway from HNSCC without HPV infection. Methods: We searched Pubmed collection for open access and English language articles publish access from years 2016-2022 with keyword HPV, HNSCC and carcinogenesis. Results: We had 16 articles that matched from the keywords. The mechanism of HPV leading carcinogenesis in HNSCC because the HPV has a specific protein that can cause malignant transformation in squamous epithelial cells. The E6 protein inactivates the p53 tumor suppressor gene by activating the ubiquitin ligase E6AP causing degradation of p53. The E7 protein inactivates the pRb (protein retinoblastoma) tumpr suppressor protein by blocking the interaction between pRb and E2F, causing E2F depression. Conclusion: Carcinogenesis and malignant transformation in HNSCC correlated with HPV infection (high risk type) via the E6 and E7 proteins. This combination can causes abnormal cell cycle and leads cells to escape cell cycle control and get a malignant transformation.